Emotions and Political Unrest - Francesco Passarelli; Guido Tabellini (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper formulates a general theory of how political unrest influences public policy. Political unrest is motivated by emotions. Individuals engage in protests if they are aggrieved and feel that they have been treated unfairly. This reaction is predictable because individuals have a consistent view of what is fair. This framework yields novel insights about the sources of political influence of different groups in society. Even if the government is benevolent and all groups have access to the same technology for political participation, equilibrium policy can be distorted. Individuals form their view of what is fair taking into account the current state of the world. If fewer aggregate resources are available, individuals accept a lower level of welfare. This resignation effect in turn induces a benevolent government to procrastinate unpleasant policy choices.
Keywords: H00; 330; emotions; political economics; unrest; riots; fairness; public debt; procrastination